2018
DOI: 10.1002/bit.26603
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms driving the lactate switch in Chinese hamster ovary cells

Abstract: The metabolism of Chinese Hamster Ovary (CHO) cells in a production environment has been extensively investigated. However, a key metabolic transition, the switch from lactate production to lactate consumption, remains enigmatic. Though commonly observed in CHO cultures, the mechanism(s) by which this metabolic shift is triggered is unknown. Despite this, efforts to control the switch have emerged due to the association of lactate consumption with improved cell growth and productivity. This review aims to cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 96 publications
5
69
0
3
Order By: Relevance
“…Taking this into account it was possible to capture the increase of ATP concentration observed in the experimental data after glucose and glutamine, and subsequently, pyruvate, were depleted (Figure 3d and further discussion on energy metabolism and product formation in the next section). Lactate consumption by cells has also been observed in other cell lines under different cultivation conditions, and might be controlled by signaling cascades (Genzel et al, 2005; Genzel, Fischer, & Reichl, 2006; Hartley, Walker, Chung, & Morten, 2018; Martínez et al, 2013; Mulukutla et al, 2015; Ryll, Valley, & Wagner, 1994; Schmid & Blanch, 1992; Xie et al, 2015). As an example, for the parental cell line AGE1.HN lactate production has been correlated with PDK4 gene inhibition (Scholz et al, 2011), and in other continuous cell lines its consumption correlated with lactic acidosis (Xie et al, 2015).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Taking this into account it was possible to capture the increase of ATP concentration observed in the experimental data after glucose and glutamine, and subsequently, pyruvate, were depleted (Figure 3d and further discussion on energy metabolism and product formation in the next section). Lactate consumption by cells has also been observed in other cell lines under different cultivation conditions, and might be controlled by signaling cascades (Genzel et al, 2005; Genzel, Fischer, & Reichl, 2006; Hartley, Walker, Chung, & Morten, 2018; Martínez et al, 2013; Mulukutla et al, 2015; Ryll, Valley, & Wagner, 1994; Schmid & Blanch, 1992; Xie et al, 2015). As an example, for the parental cell line AGE1.HN lactate production has been correlated with PDK4 gene inhibition (Scholz et al, 2011), and in other continuous cell lines its consumption correlated with lactic acidosis (Xie et al, 2015).…”
Section: Resultsmentioning
confidence: 92%
“…lines under different cultivation conditions, and might be controlled by signaling cascades (Genzel et al, 2005;Genzel, Fischer, & Reichl, 2006;Hartley, Walker, Chung, & Morten, 2018;Martínez et al, 2013;Mulukutla et al, 2015;Ryll, Valley, & Wagner, 1994;Schmid & Blanch, 1992;Xie et al, 2015). As an example, for the parental cell line AGE1.HN lactate production has been correlated with PDK4 gene inhibition (Scholz et al, 2011), and in other continuous cell lines its consumption correlated with lactic acidosis (Xie et al, 2015).…”
Section: Lactate Consumption By Cells Has Also Been Observed In Othermentioning
confidence: 99%
“…The dilution rate was subsequently reduced to an average of 0.3 and 0.33 vvd and later further to 0.21 and 0.25 vvd, for the low‐ and high‐density CSTR conditions (Figure b). On Days 22 and 26, HIPDOG control in the high and low‐density CSTRs, respectively, was stopped as it was observed that non‐limiting levels of residual glucose in each culture no longer led to significant production of lactic acid (see Figure S2 in Supporting Information), presumably due to reduced cell proliferation (Hartley, Walker, Chung, & Morten, ; Ma et al, ; Mulukutla, Gramer, & Hu, ; Vander Heiden, Cantley, & Thompson, ; Young, ; Zheng, ). On Day 31, the bleed rate to each CSTR was reduced to 0.14 (low‐density condition) and 0.15 vvd (high‐density condition), now simulating an N‐1 to CSTR working volume ratio of 1:10 (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…The lactate metabolism with metabolic dysfunctions (known as "Warburgeffect") including high formation rates at the beginning of the cultivation, followed by a stagnation of lactate accumulation, and the switch to lactate uptake is still investigated in research ( Hartley et al, 2018;Ulonska et al, 2018;Zalai et al, 2015 ). As an example, Hartley et al (2018) reviewed current theories (e.g., pH, pyruvate availability, mitochondrial function) regarding the lactate metabolism, and hypothesized that lactate consumption is a function of the cellular redox state ( Hartley et al, 2018 ). For the here aimed computational evaluation of process strategies during scaleup, a kinetic description of cell growth and metabolism was targeted and the prediction of the lactate dynamics is therefore seen sufficient.…”
Section: Mc-based Uncertainty Quantificationmentioning
confidence: 99%